Growth Response of Reef-Building Corals to Ocean Acidification Is Mediated by Interplay of Taxon-Specific Physiological Parameters - Martins, Catarina P. P.; Arnold, Angelina L.; Kömpf, Katharina; Schubert, Patrick; Ziegler, Maren; Wilke, Thomas; Reichert, Jessica (Frontiers in Marine Science, 2022)
Ocean acidification (OA) poses a major threat to calcifying organisms such as reef-building corals, typically leading to reduced calcification rates. Mechanisms to compensate the effects of OA on coral growth may, however, involve processes other than calcification. Yet, the physiological patterns mediating coral growth under OA are not fully understood, despite an extensive body of literature characterizing physiological changes in corals under OA. Therefore, we conducted a three-month laboratory experiment with six scleractinian coral species (Acropora humilis, Acropora millepora, Pocillopora damicornis, Pocillopora verrucosa, Porites cylindrica, and Porites lutea) to assess physiological parameters that potentially characterize growth (calcification, volume, and surface area), maintenance (tissue biomass, and lipid and protein content), and cellular stress (apoptotic activity) response under ambient (pH 7.9) and low pH (pH 7.7). We identified genus- and species-specific physiological parameters potentially mediating the observed growth responses to low pH. We found no significant changes in calcification but species showed decreasing growth in volume and surface area, which occurred alongside changes in maintenance and cellular stress parameters that differed between genera and species. Acropora spp. showed elevated cellular stress and Pocillopora spp. showed changes in maintenance-associated parameters, while both genera largely maintained growth under low pH. Conversely, Porites spp. experienced the largest decreases in volume growth but showed no major changes in parameters related to maintenance or cellular stress. Our findings indicate that growth- and calcification-related responses alone may not fully reflect coral susceptibility to OA. They may also contribute to a better understanding of the complex physiological processes leading to differential growth changes of reef-building corals in response to low pH conditions.